Patients’ preference of public and private hospitals: evidence from Kumasi and Bibiani in The Ashanti & Western Regions of Ghana - Amponsah, Eric (2016)
A thesis submitted to The Department of Marketing and Corporate Strategy, College of Humanities and Social Science in partial fulfillment of the requirement for the degree of Master of Business Administration (Strategic Management Option).